Oczyszczenie ludu Bożego z grzechów w świetle Listu do Hebrajczyków - Dariusz Adamczyk (Wrocławski Przegląd Teologiczny, 2020)
According to Hebrews purification of people of God from sins was made in excellent degree by Jesus Christ, who is shown like a originator of eternal salvation in prospect of Old Covenant in fight with sin. In this way in expiatory sacrifice like sacrifice of New Covenant is contained realization of Old Testament promise of put away all sins all over the world. Single and unique sacrifice of Jesus Christ effectively and definitively replaces all sacrifices from Old Testament. Still exists danger of committing the sin and off from her saving effects, what in prospect of New Covenant causes tragic consequences